Berilah Aku Minum - Arif Yupiter Gulo (Sekolah Tinggi Teologi Jaffray Jakarta, 2020)
God creates the differences and diversity. That is why it cannot be avoided. Even thought the differences and diversity are very useful to complement each other, on the other hand, it become the threats and challenges in building good relationships with others, especially in realizing God’s planning for conveying of the gospel. This research was developed using a qualitative approach that specifically refers to exegetical studies. Through apparatus studies, analysis and syntax, as well as interpretive narrative studies of the text of John 4:7b. this research emphasizes the attitude of the people of God to break down the separation and opening himself up to accept the existence of other so that the conveying of the gospel can be realized and achieved according to God’s will